Дослідження точності локалізації в сенсорних мережах при застосуванні методу мультилатерації - Кузьмін, О. В.; Kuzmin, O. V. (Видавництво Львівської політехніки, 2023)
Запропоновано для задачі локалізації сенсорних мереж використати метод мультилатерації. Ця задача може бути вирішена, якщо кожний нод буде мати у своєму складі GPS приймач. Але такі ноди дорожчі і для мереж різного призначення можна використовувати ноди без наявності GPS. Для таких мереж застосовуються так звані якірні ноди, координати яких відомі. Вони складають деякий відсоток від загальної кількості нодів. Вони використовуються для знаходження координат решти нодів, які входять до складу мережі. Якщо застосовуються тільки якірні ноди для задачі позиціонування, то такі мережі називаються некооперативні мережі. Якщо в позиціонуванні нодів приймають участь всі ноди, то такі мережі називаються кооперативними. Опимано методи розв’язку задачі локалізації сенсорних мереж, такі як: метод трилатерації, мультилатерації. Проаналізовано методи визначення відстаней між нодами сенсорної мережі, а саме: TDOA, DOA, TOA, RTT, RSSI. Розроблено алгоритм моделювання процесу локалізації сенсорних мереж методом мультилатерації. Побудовано імітаційну модель для дослідження впливу метода мультилатерації на точність визначення координат нодів. Проведені експерименти з розробленою моделлю і отримані результати цих досліджень. Кількість якірних нодів змінювалася і обчислювалась при цьому похибка позиціонування. Для більшої статистичної значимості експерименти повторювалися певну кількість разів при зміні початкового значення генератора рівномірно розподілених випадкових чисел і підраховувалося при цьому середнє значення похибки локалізації, а також мінімальне та максимальне значення. Отримані статистичні дані відображені у вигляді відповідних графіків.

One of the main tasks of deploying sensor networks is determining the coordinates of nodes that are unknown at their initial placement. This problem is known as the localization problem of sensor networks. It can be solved if each node has a GPS receiver in its composition. However, such nodes are more expensive, and for networks of various purposes, for example, environmental monitoring, fixation of moving objects in a certain area, various types of IoT, and others, nodes without GPS can be used. To solve the problem of localization in such networks, so-called anchor nodes are used, the coordinates of which are known. They form a certain percentage of the total number of nodes. They are used to find the coordinates of the remaining nodes that are part of the network. If only anchor nodes are used for the localization problem, then such networks are called non-cooperative networks. If all nodes participate in the positioning of nodes, then such networks are called cooperative. Different methods are used to solve this problem such as the method of trilateration, multilateration, triangulation, random, and others. To apply these methods, it is necessary to know the distances or angles to nodes whose coordinates are determined based on the nodes with known coordinates. At the same time, various methods are used to determine distances, namely: TDOA, DOA, TOA, RTT, RSSI. Corresponding means in modern nodes are present as separate functions. For example, the IEEE 802.15.4 (ZigBee) standard. In this paper, studies of the influence of the multilateration method on the accuracy of determining the coordinates of nodes were carried out. An algorithm was used, according to which the position of the node, for which the coordinates should be determined, was generated, as well as the coordinates of the anchor nodes that take part in the localization of the node. The distance measurement error according to the ZigBee standard with a range of 1000 m was taken as 10 %. The number of anchor nodes was changed throughout the analysis, and the respective positioning error was calculated. For greater statistical significance, the experiments were repeated a certain number of times while changing the initial value of the generator of uniformly distributed random numbers, and at the same time, the average value of the localization error, and the minimum and maximum values were calculated. The obtained statistical data were visualized in the form of relevant graphs. As a result of research, it was determined that six anchor nodes are enough to obtain a positioning accuracy of 10 m.
Study of localization accuracy in sensor networks that utilize multilateration method
Keywords: GPS; сенсорна мережа; нод; мультилатерація; GPS; sensor network; node; multilaration; functions; formulas of central finite differences; calculation of derivatives